Obstetric and Perinatal Outcomes of Pregnancies After Infertility Treatment Using Assisted Reproductive Technologies With Cryopreserved Embryo Transfer - Ryabenko, Olena P.; Mykytenko, Dmytro O. (Problems of Cryobiology and Cryomedicine, 2018)
The paper presents an analysis of the data on obstetric and perinatal outcomes of pregnancies after infertility treatment by the methods of assisted reproductive technologies (ART) using the transfer of one selected cryopreserved embryo, particularly the outcomes of spontaneous and induced singleton pregnancies. The clinical and anamnestic data of patients were analyzed. The course of pregnancy, childbirth and the state of the newborn were assessed using the data of individual medical record of the pregnant woman and discharge report from the maternity hospital. The criteria for assessing obstetric and perinatal outcomes included: the frequency of normal physiological and preterm delivery, the method of delivery and the weight of children at birth. Factors influencing the course of pregnancy and the condition of children born after natural conception and the use of ART have been determined. It was found that in a group of patients with transfer of a cryopreserved embryo of delivery by cesarean section are performed more often. The body mass index of newborns was statistically and significantly higher than in the groups with spontaneous and induced pregnancies: (3,653.3 ± 550.5) (3,420.2± 547.1) and (3,087.1 ± 704.7) g, respectively. Probl Cryobiol Cryomed 2018; 28(3): 249–257